Manajemen Produksi Program Berita di iNews TV Bandung - Susanti, Santi; Ratmita, Reksa Anggia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2020)
One of the functions of the mass media is to provide information to the public. Television, as part of the mass media, also contributes to providing information to the audiences. A diverse audience making television broadcast owners strives to meet the needs of their viewers. One of them is establishing news television, which broadcasts more information and news for viewers. Although the number of viewers is not as many as entertainment television viewers, the existence of news television is still needed, and one that is still broadcasting is iNews TV Bandung, a local television, which is the representative of iNews TV Jakarta, which is given the authority to broadcast local nuanced information. This study describes the production process of news programs on iNews TV Bandung. The research method used is descriptive-qualitative, with a focus on how the production management of news programs on iNews TV Bandung is implemented. Data collection methods used interviews, observation, and document review. Based on the research results, the production management of news programs conducted at iNews TV Bandung includes the stages of pre-production, production, and post-production, involving reporters, producers, editors, voice actors, anchors and others.